Cultivating Connections: Exploring Partnership Dynamics in American Spaces Philippines - Flores, Roana Marie (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
American Corners in the Philippines are strategically located within select academic libraries, where they design and implement programs based on the six core pillars of American Spaces. Managing these programs requires extensive collaboration with diverse stakeholders to ensure effectiveness and reach target audiences. As American Spaces cycle through program creation, planning, implementation, and evaluation, a critical question arises: how do they sustain partnerships and expand opportunities? This research focuses on understanding how these partnerships are formed, managed, and sustained, and explores both American Spaces staff and partner perspectives on their involvement in collaborative programs and projects. This study employs a descriptive exploratory mixed-methods approach using document analysis of publicly available reports and two sets of semi-structured surveys based on the Framework for Collaboration by Saunders and Corning which are completed by American Spaces staff and their referred partners. The findings revealed that the American Spaces Philippines network usually partners with educational institutions such as public/private universities and schools, USGAA, youth organizations and local community groups. These partnerships are identified based on previous engagement or word of mouth and formalized through informal methods such as verbal and email agreements though some partners may require structured agreements. Findings also showed how the American Spaces Philippines network nurtures and supports partnerships through different strategies on relationship building, communication, and the use of various tools and resources. In terms of partnership barriers, funding emerged as a moderate barrier, mainly affecting partners than American Spaces. Whereas human resources and time-related barriers are more pronounced with American Spaces than with partners. The insights gained from this research support more effective and sustainable collaborations beyond the American Spaces network. Given that all American Corners in the Philippines are supervised by libraries, this research is also valuable for library managers, as well as other project managers and leaders within the global American Spaces network and similar organizations, as it explores the often-overlooked realities of partnerships. By shedding light on these dynamics, the study assists them in enhancing their decision-making skills and helps them develop strong and effective partnership strategies.